Rancang Bangun Alat Pengukur Suhu Tubuh Non Contact dilengkapi dengan Dispenser Hand Sanitizer Otomatis - Sepannur Bandri; Rafika Andari; Andi Muhammad Nur Putra; Anggun Kemala; Zuriman Anthony (G-Tech: Jurnal Teknologi Terapan, 2024)
Body temperature measurements in certain hospitals still rely on Thermogun alongside the manual use of hand sanitizers. However, this manual approach is considered inefficient due to the repeated touching of its upper handle, which increases the risk of virus transmission among visitors. Therefore, the objective of this research is to transform the Thermogun into a contactless human body temperature measuring device, equipped with an automatic hand sanitizer dispenser and a hand sanitizer residue detector. This tool will utilize fuzzy logic algorithms to enhance accuracy, efficiency, and cost-effectiveness in temperature measurement. The design of this tool will incorporate a non-contact body temperature sensor like MLX9016, with an Infrared sensor serving as a trigger for temperature readings. Consequently, it is anticipated that the results of this research will yield a more sophisticated, responsive, and still accurate temperature measurement solution through the utilization of the MLX90614 temperature sensor.